An imaging-based analysis of lipid deposits on contact lens surfaces. Issue 4 (August 2018) - Panthi, Shyam; Nichols, Jason J.
Highlights: LipidTOX (a novel lipophilic dye) can stain lipid deposits on contact lens surfaces. Surface area of the deposits can be analyzed using the described procedure. Lipid deposition on various commercial contact lens materials is not significantly different at the central 2 mm region. Abstract: Purpose: To evaluate whether LipidTOX could stain lipid deposits on contact lens (CL) surfaces and compare lipid deposition patterns on various CL surfaces using an imaging method. Methods: Ten CLs each of six silicone hydrogel materials and one hydrogel material were incubated in cholesteryl oleate solution (5.60 mg/ml) for 12 hours. The CLs were then separately stained with Oil Red O and LipidTOX and imaged under a fluorescence microscope. Twenty worn senofilcon A CLs from both eyes of ten participants were also stained similarly. The area of deposition was calculated using Fiji software. Median deposition areas were compared between various materials using the Kruskal-Wallis test. The Mann-Whitney U test was used to compare the median deposition areas in the same material using the two dyes and also to compare the median deposition areas on worn and doped senofilcon A CLs. Results: LipidTOX staining needed fewer steps than Oil Red O for staining the deposits. There was no statistically significant difference between the median areas of lipid deposition among the CL materials using either Oil Red O (p = 0.42) or LipidTOX (p = 0.21). However, significantly different median deposition areas were found between in vitro and ex vivo stained senofilcon A CLs using both Oil Red O (p = 0.002) and LipidTOX (p = 0.029). Conclusions: LipidTOX can stain lipid deposits on contact lens surfaces and is simpler to use than Oil Red O. Lipid deposition in the central 2 mm diameter zone did not significantly differ between various commercial CL materials.